Odpowiedzi

2010-03-29T19:31:30+02:00
A)(4-2x)-(x+3)=(x-5)+(-3-x)
4-2x-x-3 = x-5-3-x
1-3x=-8
-3x=-9
x=3

b)(3-2x)+(3x+4)=-(3-2x)+(5x+4)
3-2x+3x+4=-3+2x+5x+4
7+x=1+7x
6=6x
1=x

c)-(x+3)+(2x-1)=(1+4x)+(3+x)
-x-3+2x-1=1+4x+3+x
-4+x=4+5x
-8=4x
x=-2

d)-(x+3)-(2x+8)=(-3-2x)+(2x+1)
-x+3-2x-8=-3-2x+2x+1
-3x-5=-2
-3x=3
x=-1
2010-03-29T19:32:26+02:00
A) (4-2x)-(x+3)=(x-5)+(-3-x)
4-2x-x-3-x+5+3+x=0
-3x=-9//(-3)
x=3
b) (3-2x)+(3x+4)=-(3-2x)+(5x+4)
3-2x+3x+4+3-2x-5x-4=0
-6x=-6//(-6)
x=1
c) -(x+3)+(2x-1)=(1+4x)+(3+x)
-x-3+2x-1-1-4x-3-x=0
-4x=8//(-4)
x= -2
d) -(x+3)-(2x+8)=(-3-2x)+(2x+1)
-x-3-2x-8+3+2x-2x-1=0
-3x=9//(-3)
x= -3